PELATIHAN DESAIN BAHAN AJAR DIGITAL TERINTEGRASI KOMPETENSI SOSIAL-EMOSIONAL UNTUK MENGATASI PERUNDUNGAN DI SEKOLAH PESISIR - Purwati, Diana; Bulan, Arif; Budiman, Budiman (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The training on designing digital teaching materials integrated with Social-Emotional Competence (SEC) aims to enhance teachers' competencies in developing effective teaching materials and integrating SEC into the learning process to address bullying in coastal schools. This study was conducted at SMPN 1 Hu'u, involving 40 teachers as participants. The community service activity consisted of several stages: planning, implementation, monitoring, and evaluation. The training included two days of intensive activities and one day of mentoring, where teachers were trained to design digital teaching materials that not only support academic learning but also foster students' social-emotional competence. The results of the training showed a significant improvement in teachers' skills in creating digital teaching materials and a deeper understanding of the importance of integrating SEC to address bullying in the school environment. This study confirms that such training is effective in empowering teachers to create a more inclusive and supportive learning environment